(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
In this article The patterns of occurrence and determination of the main kinetic parameters of hydrocatalytic reactions and hydrotreating processes of various hydrocarbon feedstocks in the presence of synthesized catalysts were studied. The composition and structure of the active component and active centers of transition metal sulfides, as well as methods for the synthesis of catalysts, are described. Special attention is paid to the features of hydrotreating olefin-containing raw materials.